Outcomes of Usual Versus a Specialized Falls and Balance Program in the Home. (May 2015) - Whitney, Susan L.; Marchetti, Gregory F.; Ellis, Jennifer L.; Otis, Laurie
Abstract : A retrospective cohort study with adjustment for baseline group differences was conducted to determine if there was a difference in Outcome and Information Data Set (OASIS-C) activities of daily living (ADL) outcomes as well as the duration and number of home care visits between usual home care rehabilitation services and a home care rehabilitation team that was specially trained in falls identification and prevention. Data from adult Medicare beneficiaries who were treated in a large multistate home care practice with at least one visit by a physical therapist were retrieved retrospectively for analysis (n = 3, 907 records). Patients identified as having multiple fall risk factors based on OASIS-C assessment undergoing a specialized care program demonstrated greater improvements in mean total ADL scores after home healthcare rehabilitation services compared with subjects at fall risk receiving usual care. Interdisciplinary care delivered by a healthcare team specially trained in fall prevention appeared to decrease the number of home care visits and resulted in improved ADL OASIS-C outcome scores after adjustment for potential confounders.